A 2010-14 közötti államosítások történelmi előzményei Magyarországon, 1722-1962 - Péter Mihályi (Hungarian Academy of Sciences, Institute of Economics, 2015)
– One of the intriguing questions of our times is the importance of the centralization and nationalization campaigns of the 2nd and 3rd Orbán-government carried out since 2010. In an earlier working paper - Mihalyi (2015) - I demonstrated that similar policy steps were occasionally taken in other post-socialist countries, too. It is also a known fact, that the subsequent Hungarian governments in the 1990-2010 period were also forced in some cases to renationalize already privatized firms - although the main trend of policies was privatization. However, in my earlier work a logical question was ignored, namely why this U-turn has been so far so easily accepted by the Hungarian society at large and many opinion leaders both on the political left and political right. One conceivable answer is that this is what the Hungarian people have been accustomed to. The history of the past 300 years was nothing else but a sequence of nationalizations and confiscations, and the milestones of this have been taught with proud already in the elementary schools for generations. From the perspective of the present paper, it doesn't matter whether the nationalizing governments could have made different decisions; whether they were pressed by outside forces or acted independently. It will be shown that the decision-makers were both prisoners of their own epoch and the ideology of their social classes, but at the same time they were also authoritative diffusers of their own ideologies through politics, education and the media. The subsequent asset redistributions in the modern economic history of Hungary aimed at accelerating the country's economic development and catching up with the more advanced economies. Unfortunately the decision-makers didn't realize that these measures - nolens volens - undermined the idea of private property, the rule of law and the trust vis-à-vis the state itself.
Keywords: N4; P20; P26; P31; P51; 330; economic history; nationalization; socialization; restitution; land reform; retroactive legislation